2012
DOI: 10.3747/co.19.890
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Surveillance for Contralateral Breast Cancer in Patients Less than Age 60 at the Time of Initial Diagnosis

Abstract: Background: After an initial diagnosis of breast cancer, the risk of contralateral breast cancer is approximately 0.5% per year. Annual mammography is recommended to identify local recurrences and contralateral new primaries. Because the sensitivity of mammography tends to be lower in younger women, we conducted a retrospective review of the method of detection and pathologic stage of metachronous contralateral primary breast cancers according to age at diagnosis in a cohort of breast cancer patients. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A number of improvements in treatment during this period have undoubtedly contributed to the improved survival rate. Previous studies have shown sex, BMI and initial pathologic diagnosis age differences in the pathophysiology, clinical presentation and treatment response of cancers, such as head and neck cancer, endometrial cancer and breast cancer ( 10 , 44 , 58 ). In the present study, we systemically investigated the effect of sex, BMI and initial pathologic diagnosis age on two- and five-year survival rates for each of the 38 different types of cancer in TCGA.…”
Section: Discussionmentioning
confidence: 99%
“…A number of improvements in treatment during this period have undoubtedly contributed to the improved survival rate. Previous studies have shown sex, BMI and initial pathologic diagnosis age differences in the pathophysiology, clinical presentation and treatment response of cancers, such as head and neck cancer, endometrial cancer and breast cancer ( 10 , 44 , 58 ). In the present study, we systemically investigated the effect of sex, BMI and initial pathologic diagnosis age on two- and five-year survival rates for each of the 38 different types of cancer in TCGA.…”
Section: Discussionmentioning
confidence: 99%